Challenges of EFL Course Retaking: Toward a Model for Remedial Reading - Hazaea, Abduljalil (Jurnal Arbitrer, 2024)
Course retaking brings pivotal challenges for learning institutions all over the world. This urges many academicians to investigate the reasons why students retake courses. Therefore, this article identifies the micro and macro challenges associated with retaking a reading course. It also generates a remedial reading model for English as foreign language (EFL) contexts. Data was collected from reading course specifications, course report, and focused group discussions with six experienced language instructors at the preparatory year program of a Saudi university. Using grounded theory, the qualitative data was analyzed through thematic analysis. The findings revealed a complex web of challenges associated with different stakeholders: the course retakers, language instructors, administration, and retakers’ families; all of them share the challenge of time constraints, especially after the shift from two to three semesters. At the micro level, course retakers struggle with poor foundational skills and demotivation, focusing on passing exams. They also lack exposure to English and seldom invest office hours for help. Language instructors struggle with learning materials, demotivation, and assessment. At the macro level, students’ families contribute to maximize these challenges. A gap exists between the intended learning outcomes and student levels and admission criteria. These challenges collectively hinder course retakers’ reading skills. The study generates a five-pillar bridging model that integrates learning outcomes, exam-oriented teaching strategies, simplified reading materials, technology-assisted reading, and motivational strategies to foster EFL remedial reading. The study recommends some pedagogical implications for remedial reading classes.